1971
DOI: 10.1002/pssa.2210050227
|View full text |Cite
|
Sign up to set email alerts
|

Creation spectra of colour centres in KCl and NaCl developed via electron emission

Abstract: The spectral dependence of the UV coloration efficiency in KCl and NaCl single crystals was measured in vacuum in the region hve = 7 to 11 eV. Photo‐ and thermostimulated electron emission was used to detect the small quantities of UV‐created colour centres. Excitons (e0) as well as electron‐hole pairs (e+ · e−) occur to be responsible for coloration even at low temperatures at which e0 and e+ become immobile. Certain differences between e0‐ and e+ · e−‐induced coloration processes are revealed. Some condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…1 a, curve 3, see also [9]). The optical [6] and ESR [17] investigations of KCl:Na crystals have also shown that HA(Na+) centres thermally decay at about 120 K. …”
Section: Resultsmentioning
confidence: 99%
“…1 a, curve 3, see also [9]). The optical [6] and ESR [17] investigations of KCl:Na crystals have also shown that HA(Na+) centres thermally decay at about 120 K. …”
Section: Resultsmentioning
confidence: 99%
“…ВУФ-радиация в области собственного поглощения ЩГК проникает только в тонкий припо-верхностный слой, и абсолютное число создаваемых там дефектов недостаточно для регистрации традиционными абсорбционными методами (оптическое поглощение или ЭПР). Поэтому о количестве созданных ВУФ-радиацией в ЩГК дефектов судили по фотостимулированной в F-полосе поглощения люминесценции специально вве-денных в кристалл примесных ионов (люминесцентный зонд) [89] или электронной эмиссии [98]. Позднее за меру созданных ВУФ-радиацией в большинстве гране-центрированных ЩГК и объемноцентрированных CsCl и CsBr α−I или F−H пар ДФ стали использовать и так называемую α-люминесценцию (излучательный распад созданного фотоном в области α-центра (ν a ) связанного e 0 ) или туннельную люминесценцию при перезарядке F * −H пар ( * означает возбужденное со-стояние, в которое при фотостимуляции переходит F-центр) [9,58,66,97,[99][100][101][102][103][104][105].…”
Section: международная школа-семинар "unclassified
“…The first step is the optical transition from the colour centre to the conduction band, and the second step is the thermionic emission from the conduction band to vacuum. The stimulation spectra (i.e., PSEE as a function of the stimulating wavelength) have been studied extensively and found to give information about the colour centres similar to that yielded by their optical absorption spectra (Ford et al 1970;Bichevin et al 1971;Nink and Holzapfel 1973;Maiste et al 1973;Kortov et al 1982;Tale et al 1982).…”
Section: 3bmentioning
confidence: 99%